PENGARUH PENDIDIKAN ISTRI PENDAPATA KELUARGA DAN PENGGUNAAN ALAT KONTRASEPSI TERHADAP TINGKAT KELAHIRAN DI KELURAHAN ELAI KOTA BONTANG - BAYU PERCEKA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this research is study and analyze the influence of wife education, income and Contraception to Fertility in the district Gunung Elai Bontang City. Basic theory used fertility theory by using multiple linear regression analysis using SPSS. This research is the couples of childbearing age with 100 samples in the district GunungElai. The results showed that Wive's level of education negative and significant effect to Fertility in the district Gunung Elai Bontang City, Income level significantly and positive related to Fertility in the district Gunung Elai Bontang City and Contraseption levels no significant and Negatife effect to Fertility in the district Gunung Elai Bontang City.Keywords: Wife Education, Income and Contraseption – Fertility